2014
DOI: 10.1128/mcb.01554-13
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Complexities of DNA-Dependent Protein Kinase Autophosphorylation

Abstract: f DNA-dependent protein kinase (DNA-PK) orchestrates DNA repair by regulating access to breaks through autophosphorylations within two clusters of sites (ABCDE and PQR). Blocking ABCDE phosphorylation (by alanine mutation) imparts a dominant negative effect, rendering cells hypersensitive to agents that cause DNA double-strand breaks. Here, a mutational approach is used to address the mechanistic basis of this dominant negative effect. Blocking ABCDE phosphorylation hypersensitizes cells to most types of DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 53 publications
8
79
1
Order By: Relevance
“…The autophosphorylation of DNA-PKcs/S2056 can be induced by ionizing radiation and other DNA damage agents [4, 7, 37], and is necessary for the activation of the DSB NHEJ repair pathway. Our study demonstrated that overexpression of TNKS1BP1 effectively induced the autophosphorylation of DNA-PKcs/S2056.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The autophosphorylation of DNA-PKcs/S2056 can be induced by ionizing radiation and other DNA damage agents [4, 7, 37], and is necessary for the activation of the DSB NHEJ repair pathway. Our study demonstrated that overexpression of TNKS1BP1 effectively induced the autophosphorylation of DNA-PKcs/S2056.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA dependent protein kinase complex (DNA-PK) is a critical component of the NHEJ pathway, which consists of a Ku70/Ku80 heterodimer and the DNA dependent protein kinase catalytic subunit (DNA-PKcs). DNA-PK plays an essential role in the pathway of NHEJ repair, including initiating DSB recognition, regulating access to breaks, promoting repair machinery assembly and DNA molecule ligation [3, 4]. As the catalytic subunit, DNA-PKcs is a member of the phosphatidylinositol-3 (PI-3) kinase-like family (PI3KK), and it is recruited to DNA damage sites by the Ku70/Ku86 heterodimer [5, 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA (30–50 µg) was hydrolyzed overnight in 1% nitric acid at 70°C in 500µL total volume. Samples were then diluted to 1.5mL final volume in 1% nitric acid and analyzed by ICP-mass spectrometry as we have previously described (24). Briefly, a benchtop series Thermo ICPMS X-series II system with collision cell technology capability and PlasmaLab software were used to quantify CDDP concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Cells deficient in various c-NHEJ factors are more sensitive to agents that induce replication stress than c-NHEJ-proficient cells (27,28,53). Schwartz et al have shown previously that fibroblasts derived from XLF-deficient patients are sensitive to low-dose aphidicolin, display increased fragile site instability, and display cell cycle disruptions consistent with an inability to resolve DNA damage associated with replication stress (16).…”
Section: Xlfmentioning
confidence: 99%